2008
DOI: 10.1007/s10646-008-0222-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of genotoxicity and effects on reproduction of nonylphenol in Oreochromis niloticus (Pisces: cichlidae)

Abstract: Nonylphenol ethoxylate (NPE) is widely used as a component of detergents, paints, pesticides, and many other products. In the aquatic environment NPE breakdown to 4-nonylphenol (NP), which is more stable and persistent. NP is estrogenic in fish, avian, and mammals and is described as an environmental pollutant with endocrine disruptor characteristics. The genotoxicity of NP was evaluated through micronuclei assay and single cell gel electrophoresis (Comet assay) in peripheral erythrocytes of Oreochromis niloti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 30 publications
0
22
0
1
Order By: Relevance
“…This assay was performed as described by (Singh et al, 1988), with some modifications for fish as previously reported by Rivero et al (2008), as described below. The cell suspension placed in the microtube was mixed with 120 µL low-melting agarose (37°C).…”
Section: Comet Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…This assay was performed as described by (Singh et al, 1988), with some modifications for fish as previously reported by Rivero et al (2008), as described below. The cell suspension placed in the microtube was mixed with 120 µL low-melting agarose (37°C).…”
Section: Comet Assaymentioning
confidence: 99%
“…It is a valuable tool for population monitoring, for example, in assessing mechanisms of mutagenesis, genotoxicity and ecological monitoring, and for investigating DNA damage and repair in different cell types in response to a range of DNA-damaging agents, among others (Dusinska and Collins, 2008;McKenna et al, 2008;Collins, 2009). Thus, the micronucleus (MN) test, assessment of nuclear abnormalities (NA) (da Silva and Fontanetti, 2006) and the comet assay are excellent techniques used in vivo to test the genotoxicity of environmental pollutants such as EDC (al-Sabti and Metcalfe, 1995;Grisolia and Starling, 2001;Pacheco and Santos, 2002;Bolognesi et al, 2006;Kim and Hyun, 2006;Rivero et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This assay was performed as described by Singh et al (1988), with some modifications for fish as previously reported by Rivero et al (2008), as described below. The cell suspension sampled in the microtubule was mixed with 120 µL low melting agarose (37°C).…”
Section: Comet Assaymentioning
confidence: 99%
“…NP is present in the environment mainly after degradation of nonylphenol ethoxylates (NPE; Soares et al, 2008). NPE is an alkylphenol widely utilized in the non-ionic surfactant industry, lubricants, antioxidants, detergents, paints, insecticides and herbicides, and also used as a stabilizer in plastic polymers (Oliveira-Filho et al, 2005;Rivero et al, 2008). Many studies show the presence of this pollutant in sewage, sediments, rivers and drinking water (Tsuda et al, 2000;Berryman et al, 2004;Shao et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Estrogenic action of NP is described for diverse animals, including birds (Razia et al, 2006), fish (Rivero et al, 2008) and mammals (Chapin et al, 1999;Tagaki et al, 2004). The median lethal dose of NP in male adult mice is 170 mg/kg body weight (b.w.)…”
Section: Introductionmentioning
confidence: 99%